Facilitating torrance test of creative thinking use in Malaysian TVET research: the initial step of inter-rater reliability determination - Madar, Ahmad Rizal; Chew, Eng Sun; Hamid, Hashima (Penerbit UTHM, 2019)
Creativity is a valuable 21st century attribute, vital to innovation, and is considered as an important aspect in technical and vocational education and training (TVET). This study is prompted by the lack of international test use in Malaysian TVET creativity-related research where the Torrance Tests of Creative Thinking (TTCT), translated into the Malay Language (ML) could fill in this gap. The determination of inter-rater reliability coefficients cover five norm-referenced dimensions or measures of figural creativity, viz. fluency, originality, elaboration, resistance to premature closure, abstractness of titles, and the overall average score for the TTCT (Form A). This study involves correlation research where subjective answers to TTCT (ML) by 35 prospective teachers from a Teacher Education Institute - Temenggong Ibrahim Campus, Johor Baharu were marked by 3 independent raters, and subsequently analysed for correlations. Data analyses of IRC were carried out using interclass correlation analysis found in the Statistical Package for Social Science (SPSS) software. Excellent IRC values were obtained as follows: Fluency (.99), Originality (.99), Elaboration (.90), Resistance to Premature Closure (.93), Abstractness of Titles (.98), and overall average score (.99), with r≥.9. The IRC values obtained for the TTCT (ML) version are consistent with values obtained for the English (international) TTCT version, viz. r, from.78 to.99. In conclusion, the TTCT (ML) version is valid and reliable data collection instrument for research on creativity, innovation or higher-order thinking skills involving TVET respondents whose mother tongue is Malay.